Ecology of Indian Fox Vulpes bengalensis (Shaw, 1800) in and Around Tal Chhapar Wildlife Sanctuary, Rajasthan, India - Dookia, Sumit; Das, Sanjay K., Rajlakshmi (Indian Forester, 2012)
The present study deals with ecological observations on Indian fox (Vulpes bengalensis) in the Tal Chhapar Wildlife Sanctuary, Rajasthan during monsoon season that coincides with pup rearing period of this animal. Though the sanctuary holds a small population of about three breeding pairs of Indian fox, it serves as a safe breeding ground for source population of the nearby areas. The study showed if the temperature is mild and food is abundant, as on rainy days, the fox may also hunt at mid-day and show bimodal activity in the absence of large predators and any kind of other disturbances. During pup rearing season, most of the time the animal spent in sitting/resting, followed by searching for food and other minor activities. Parental care also found in this animal. Preference for particular den opening by the adults was observed for entry and exist which suggests that adults are well versed of their dens to escape from their predators. Both from food availability sampling and scat analysis, insects were found to be the main food item of this animal during the study period which shows that they are selective in their food habit in the monsoon season, as the availability of insects is all time high in these days. The basic social unit of this animal was found to be restricted to individual family level.